PENERAPAN BUDAYA ORGANISASI - Esthiningtyas, Rina Budi; Murtini, Wiedy; Rahmanto, Andre N (Pendidikan Administrasi Perkantoran FKIP Univesitas Sebelas Maret, 2012)
Abstract: The aim of this research are to know application organization culture that there in Secretariat Legislative Assembly at Regency of Surakarta, constraint in application organization culture that declared in office Secretariat Legislative Assembly at Regency of Surakarta, and solution to grow up a good organization culture in office Secretariat Legislative Assembly at Regency of Surakarta. This research is qualitative research with descriptive method. Based on research we it can be concluded that: Application organization culture in Secretariat Legislative Assembly at Regency of Surakarta is polite attitude and must have job discipline and must professional. The problem in application organization culture in Secretariat Legislative Assembly at Regency of Surakarta is: (a) socialization process is not optimal, (b) a bad understanding about organization culture. Solution to solve problem an application organization culture in Secretariat Legislative Assembly at Regency of Surakarta is: (a) Often inform organization culture, (b) Giving the good understanding about organization culture.Keyword: Organization Culture, Secretariat Legislative Assembly